2017
DOI: 10.1186/s12893-017-0277-z
|View full text |Cite
|
Sign up to set email alerts
|

Intended cost reduction in laparoscopic appendectomy by introducing the endoloop: a single center experience

Abstract: BackgroundCost reduction measures in medicine are gaining greater importance nowadays, especially in high-volume procedures such as laparoscopic appendectomy (LAE). Currently there are two common methods of dissecting the appendix from the caecal pole: linear stapler and endoloops. The endoloop is the cheaper device but can only be used in uncomplicated cases of appendicitis. Therefore both methods are used in LAE depending on intraoperative findings. The goal of this study was to retrospectively evaluate poss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 25 publications
0
15
0
Order By: Relevance
“…Relatedly, the incidence of postoperative complications is a key quality metric for evaluating surgeon and hospital performance [28][29][30][31][32][33][34][35]. In over 4000 consecutive patients with acute appendicitis, the overall 90-day incidence of postoperative complications following appendectomy was 12.6%.…”
Section: Discussionmentioning
confidence: 99%
“…Relatedly, the incidence of postoperative complications is a key quality metric for evaluating surgeon and hospital performance [28][29][30][31][32][33][34][35]. In over 4000 consecutive patients with acute appendicitis, the overall 90-day incidence of postoperative complications following appendectomy was 12.6%.…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that LA is performed more frequently in high-income countries in comparison to low-income countries (67.7% vs 8.1%), with better postoperative outcomes[ 54 ]. The difference in the costs of the used surgical devices (above all stapler) represented a principal determinant for the overall economic impact of the surgical procedure in some recent reports[ 33 , 36 , 38 , 50 , 51 ], to highlight how important is the cost-effectiveness in the measured outcomes. The medium saving reported in the present paper is relevant, varying from around approximately 300 € to more than 500 € just for the device, which then must be multiplied for the many LA conducted worldwide; further cost-analysis including operative time and LOS could reach major savings.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, it is still debated the use of endostapler (ES) vs endoloop (EL) in appendiceal stump closure[ 25 - 28 ]. The routine use of EL is safe in most patients affected by AA, also when it is complicated[ 29 - 32 ], representing a cost-effective device when taking into consideration the additional costs of potential post-operative complications, too[ 33 - 37 ]. We have previously shown money saving as well as the safety of the routine use of ELs[ 38 ].…”
Section: Introductionmentioning
confidence: 99%
“…Miyano et al 13 refer that, in the USA, average operating cost using endoloop is USD $ 890, while using the stapler it is USD $ 1,300. Mehdorn et al 10 report that, in Germany, the use of the stapler is € 235 more expensive than the use of endoloop.…”
Section: Discussionmentioning
confidence: 99%